Natural Oestrogen in the Female Climacteric - Influence on Blood Coagulation and Fibrinolysis - Lagrelius, Anders; Lunell, Nils-Olov; Blombäck, Margareta (Thrombosis and Haemostasis, 1978)
The aim of the present study was to investigate the effect on blood coagulation and fibrinolysis of a natural oestrogen preparation, piperazine oestrone sulphate, prospectively in menopausal women. Scopolamine was given to the control group.The women were investigated before and during treatment with regard to factors VIII, VII, X, V, fibrinopeptide A, antithrombin III, plasminogen, rapid antiplasmin and α1-antitrypsin. There was no significant change towards hypercoagulability or decreased fibrinolysis in any group. In the oestrogen group, however, a tendency towards an increased level of plasminogen and a decreased level of antiplasmin was demonstrated. In the scopolamine group there was an unexpected fall in factors X and V and also in plasminogen and α1,-antitrypsin. A low level of some blood coagulation factors in some of the women before treatment is somewhat astonishing; none of them had any history of excessive bleeding.